Deconstructability prediction for building using machine learning and ensemble feature selection techniques - Habeeb Balogun; Hafiz Alaka; Eren Demir; Christian Nnaemeka Egwim; Godoyon Ebenezer Wusu; Wasiu Yusuf; Muideen Adegoke; Iqbal Qasim (Scientific Reports)
Abstract Construction industries remain one of the most significant users of materials and generators of waste in the UK and globally. Notwithstanding, the principle of circular economy is becoming prominent as an effective means for powering greater resource efficiency. It has the prospect of unlocking significant economic value, particularly at the building end of useful life through reuse. A noteworthy end-of-life practice which aligns with this idea is deconstruction, which is the careful disassembly of the building into components and sub-components for reuse. However, deconstruction is not meant for all buildings, and this is because a typical building is constructed as a permanent product waiting to be disposed of after use. Laying on this foundation, assessing the building for deconstruction is necessary, and it is mainly done via several manual inspections, which may be expensive and time-consuming. A deconstructability predictive model using a machine learning-based model and ensemble feature selection techniques was developed to tackle this problem. This paper elaborates on the model creation and illustrates its application through a real-world deconstruction project.